(untitled) (Herald of Journalism, 2016)
Мақалада қазақстандық журналистердің арасында жүргізілген социологиялық сұрау статистикалық мәліметтері келтірілген. Барлық нәтижелер пайыздарда ұсынылған. Автор осы ғылыми зерттеуінде Қазақстандағы қазіргі журналистика жағдайын түгелге жуық қамтып көрсетеді. Деректердің жинағы осы кәсіптің даму бағыттарына әрі үрдістеріне болжам жасауға көмектеседі. In this article the statistical data of the sociological poll, that was spent among the Kazakhstan’s journalists, are placed. All the results are presented in percentage. Research almost completely reflects position in which there is a modern journalism of Kazakhstan. The collected facts allow to predict the further tendencies of development of this profession. High enough percentage indicators of lack of the qualified specialists in the field of journalism - the certificate that the conditions, created for their work in The Republic of Kazakhstan, do not answer the accepted norms.